Pengaruh Kulit Langsat (Lansium Domesticum) Yang Diimobilisasi Dengan Natrium Silikat Terhadap Penyerapan Ion Logam Zn2+ Dalam Larutan - Addawiyah, Nadiyatul; Kurniawati, Desy (Departemen Kimia FMIPA UNP, 2023)
Zinc is the fourth most used metal after iron, aluminum and copper and and it pollutes terrestrial and aquatic ecosystems. The primary issue with zinc is that it is non-biodegradable and will build up in water. To overcome this Zn metal, biosorption employs a batch method by using langsat peel immobilized with sodium silicate as a biosorbent, which is more efficient, environmentally friendly, and improves the adsorbent performance in the adsorption process. In this study, the parameters tested were variations in pH, solution concentration, particle size, contact time, and variations in stirring speed. The results showed that the maximum absorption capacity of the metal ion Zn2+ using sodium silicate immobilized langsat peel obtained through the Langmuir isotherm equation was 20.4081 mg/g in optimum state of the adsorption process at pH 4, solution concentration 300 ppm, particle size 150 m, time contact for 90 minutes and the stirring speed of 200 rpm.